PROBLEMATIKA PENDANAAN PENGADAAN TANAH PROYEK STRATEGIS NASIONAL MELALUI KONSINYASI PENGADILAN NEGERI - Robiah Adawiyah, (Sekolah Tinggi Ilmu Al-Qur'an Amuntai, 2023)
Acquiring land involves finding its rightful owners and compensating them fairly for their property. This involves phases for preparation, execution, and the presentation of outcomes. According to Law 2 of 2012, the government is responsible for acquiring land for development in the public interest. For the greater good, the government is authorised by Presidential Decree No. 109 of 2020 to acquire property in order to put into motion National Strategic Projects (PSN). Since PMK No. 139/2020 and Perma 2/2021 have conflicting requirements, only a select number of PSNs will be allowed. In light of Indonesia's legislative framework, this study seeks to identify the challenges associated with financing land purchase for National Strategic Projects through District Court Consignment. This paper uses a normative judicial research methodology and a statutory approach. This study's findings clarify the need for the two sets of rules to be harmonised via coordinated efforts to secure money for land acquisition. The result was the implementation of rules by the Ministry of Finance.